Range expansion and migration of Trumpeter Swans Cygnus buccinator re-introduced in southwest and central Ontario - Handrigan, Sara A.; Schummer, Michael L.; Petrie, Scott A.; Norris, D. Ryan (Wildfowl, 2016)
Trumpeter Swans Cygnus buccinator were extirpated from Ontario in 1886 as a result of unregulated subsistence and market hunting. Between 1982–2006 inclusive, 584 captive reared Trumpeter Swans were released in southern Ontario, to re-introduce the species to the region. However, no empirical analysis of the size of the breeding range has occurred since the reintroduction programme commenced. Observational data recorded from 1,394 captive-released and wild-hatched swans marked with uniquely identifiable patagial tags therefore were analysed, using a kernel density spatial framework, to infer changes in breeding distribution. The breeding range increased 16 fold between 1991 (301,938 ha) and 2010 (4,817,904 ha). A linear effect of year best explained breeding range expansion from 1991–2010. However, visual inspection of the relationship suggests that the breeding range did not increase after 2004, which coincided closely with the end of the reintroduction programme in 2006. Migration distances calculated for adult male and female, captive-released and wild-hatched swans from 1982–2010 showed that most swan breeding and wintering locations were close to release sites (median migration distance = 4.6 km, range = 0– 1,299 km) and 40% of swans were non-migratory (wintering and breeding locations were the same). The model that best explained migration distance included a quadratic fit of year, sex, and status (captive-released vs. wild-hatched birds). Migration distance declined until about year 2000 and then increased thereafter.